Formulation and In Vitro Evaluation of Mucoadhesive Antimicrobial Vaginal Tablets of Ciprofloxacin Hydrochloride - Firas Aziz Rahi; Lena M Thomas (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2012)
Ciprofloxacin is a broad spectrum fluoroquinolone, effective in the treatment of a wide range of infections, including genitourinary tract infections. In this study, bioadhesive vaginal tablets of ciprofloxacin hydrochloride were prepared by direct compression method using a combination of bioadhesive polymers carbopol 934P(Cp), carboxymethylcellulose (CMC) and sodium alginate (SA) in different ratios. The prepared tablet formulations were characterized by measuring their swelling capacity, surface pH, bioadhesive properties, and in-vitro drug dissolution. It was found that the bioadhesive force was directly proportional to carbopol 934P content in different formulae and was further enhanced by the inclusion of carboxymethylcellulose. Swelling studies indicated that formulae containing a combination of carbopol 934P and sodium alginate or carboxymethylcellulose had greater swelling index than those containing carbopol 934P alone. Formulations containing Carbopol 934P and carboxymethylcellulose were found to swell to a greater extent than those composed of similar ratios of carbopol and sodium alginate. In vitro drug release study showed that the release of ciprofloxacin hydrochloride from formulae containing carboxymethylcellulose was faster than from those containing sodium alginate. Formula F5 composed of CP/CMC in a ratio of 2:1 showed moderate swelling, suitable bioadhesion and retardation of drug release. Thus, it may be considered a good candidate as a base for bioadhesive vaginal tablet